Pengaruh Penerapan Aplikasi Keuangan dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan (Studi Kasus Pada Universitas Jambi) - Lisa Lestari; Liona Efrina S; Eka Julianti Efris Saputri; Efandri Agustian; Raya Sulistyowati (Business Education Program of Universitas Pendidikan Indonesia, 2023)
This study aims to determine the effect of the application of financial applications and human resource competencies on the quality of financial statements (case study at Jambi University). This sample was taken from 40 respondents at Jambi University. The type of data used in this study is quantitative data obtained from questionnaires distributed to respondents. In this study the data sources used in data collection include primary data. The research instrument used in this study used a Likert scale. Based on the results of data research using statistical calculations through the SPSS (Statistical Package for the Social Science) version 26 application regarding the Effect of the Application of Financial Applications and Human Resource Competencies on the Quality of Financial Statements (Case Study at Jambi University), the authors can conclude that the application of financial applications and human resource competencies has a significant positive effect on the quality of financial statements. the better the application of financial applications in making financial reports, the better the quality of the resulting financial reports. and the better the competence of human resources, the better the quality of the resulting financial reports.